MSME Business Decision Analysis in Indonesia during the Covid 19 Pandemic - Moh. Hudi Setyobakti; Khoirul Ifa; Ani Yulianti; Ria Meilan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The Covid 19 pandemic in Indonesia has an impact on the sustainability of the business sector, especially MSMEs. MSME actors are faced with situations and must make decisions in the midst of environmental changes that occur. Different conditions in each MSME, both different types of business, business capacity, resource capacity, make different decision attitudes. This research is a secondary research, conducted by reviewing the articles that have been published and published in Indonesia, as many as 15 articles. The results of the study show several important decisions taken by MSMEs during the COVID-19 pandemic, including 1) Survival strategy, by making savings, 2) Optimization of the resources they have, without adding other additional resources, 3) Participation in the economic recovery program by the government includes social assistance, training and assistance, tax incentives, and credit restructuring, 4) Application of information technology such as digital marketing and financial technology transformation, 5) Personal selling improvement, 6) Product innovation, 7) Preventive steps with more mature business planning . The contribution of this research is to provide input for policy makers to pay attention to the needs of MSMEs in making decisions for business continuity, as well as developing research analysis of MSME business decisions.